2021
DOI: 10.1177/21925682211008830
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Three-Dimensional Printing Spine Model in Severe Spine Deformity Correction Surgery

Abstract: Study Design: Retrospective case-control study. Objective: We aimed to evaluate the value of 3-dimensional printing (3DP) spine model in the surgical treatment of severe spinal deformity since the prosperous development of 3DP technology. Methods: Severe scoliosis or hyper-kyphosis patients underwent posterior fixation and fusion surgery using the 3DP spine models were reviewed (3DP group). Spinal deformity surgeries operated by free-hand screw implantation during the same period were selected as the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
7
0
4
Order By: Relevance
“…Spinal deformity is a three-dimensional pathology, leading to coronal and sagittal plane decompensation, and can result in clinical complaints, neurological deficits, deformity progression, trunk imbalance and cardiopulmonary dysfunction [ 18 21 ]. Treatment of severe spinal deformity is one of the ultimate challenges for spine surgeons [ 22 ]. Literatures reported the incidence of neurological complications in spinal deformity correction surgeries was 1–27% [ 5 , 9 , 23 – 25 ], and with regard to new neurological deficits, the incidence was reported as 0.178–9.4%, and 33.6% of it was related to spinal instruments [ 9 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal deformity is a three-dimensional pathology, leading to coronal and sagittal plane decompensation, and can result in clinical complaints, neurological deficits, deformity progression, trunk imbalance and cardiopulmonary dysfunction [ 18 21 ]. Treatment of severe spinal deformity is one of the ultimate challenges for spine surgeons [ 22 ]. Literatures reported the incidence of neurological complications in spinal deformity correction surgeries was 1–27% [ 5 , 9 , 23 – 25 ], and with regard to new neurological deficits, the incidence was reported as 0.178–9.4%, and 33.6% of it was related to spinal instruments [ 9 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The life size 3D model allows simulation surgery before the real one, increases surgeons' confidence, and improves the accuracy and consistency of pedicle screw placement 16 . The main indi-cations of using such models are severe scoliosis (>100°), revision cases with distorted reference points for pedicular entry, and multiplanar complex deformities 17 . We reproduced the osseous anatomy into a 3D printed model which enabled us to plan the surgery better.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis validated the satisfactory efficacy of the 3D-printed navigation template-assisted screw placement technique in corrective surgery for AIS and CS patients, which provides a breakthrough for improving the surgical precision of this special population. [6][7][8][9] Accepted Manuscript This article is protected by copyright. All rights reserved.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In recent years, the application of the 3D-printed navigation template technique has become more and more extensive. Some studies have compared the screw placement methods between 3Dprinted navigation templates and free-hand techniques in the surgical treatment of scoliosis, [6][7][8][9] they found that the accuracy of 3D-printed navigation template-assisted screw placement may be higher than that of the free-hand technique. However, most relevant literature about 3D-printed navigation templates contained a small sample, [10][11][12][13] so there was still no clear conclusion on its actual clinical effect in spinal corrective surgery.…”
Section: Introductionmentioning
confidence: 99%